Volumetric Capnography Monitoring and Effects of Epinephrine on Volume of Carbon Dioxide Elimination during Resuscitation after Cardiac Arrest in a Swine Pediatric Ventricular Fibrillatory Arrest - Al-Subu, Awni M.; Hacker, Timothy A.; Eickhoff, Jens C.; Ofori-Amanfo, George; Eldridge, Marlowe W. (Journal of Pediatric Intensive Care, 2020)
The aim of this study was to examine the use of volumetric capnography monitoring to assess cardiopulmonary resuscitation (CPR) effectiveness by correlating it with cardiac output (CO), and to evaluate the effect of epinephrine boluses on both end-tidal carbon dioxide (EtCO2) and the volume of CO2 elimination (VCO2) in a swine ventricular fibrillation cardiac arrest model. Planned secondary analysis of data collected to investigate the use of noninvasive monitors in a pediatric swine ventricular fibrillation cardiac arrest model was performed. Twenty-eight ventricular fibrillatory arrests with open cardiac massage were conducted. During CPR, EtCO2 and VCO2 had strong correlation with CO, measured as a percentage of baseline pulmonary blood flow, with correlation coefficients of 0.83 (p < 0.001) and 0.53 (p = 0.018), respectively. However, both EtCO2 and VCO2 had weak and nonsignificant correlation with diastolic blood pressure during CPR 0.30 (p = 0.484) (95% confidence interval [CI], –0.51–0.83) and 0.25 (p = 0.566) (95% CI, –0.55–0.81), respectively. EtCO2 and VCO2 increased significantly after the first epinephrine bolus without significant change in CO. The correlations between EtCO2 and VCO2 and CO were weak 0.20 (p = 0.646) (95% CI, −0.59–0.79), and 0.27 (p = 0.543) (95% CI, −0.54–0.82) following epinephrine boluses. Continuous EtCO2 and VCO2 monitoring are potentially useful metrics to ensure effective CPR. However, transient epinephrine administration by boluses might confound the use of EtCO2 and VCO2 to guide chest compression.
Keywords: resuscitation; end-tidal CO2; volumetric capnography; VCO2; monitoring; pediatric